Financial Outcomes of Harvests Aimed at Diversifying Forests in Western Oregon and Washington - Klaus J. Puettmann; Rowan Braybrook; Seth Zuckerman; Olli-Pekka Kuusela (Small-scale Forestry, 2024)

Protected area downgrading, downsizing, and degazettement as a threat to iconic protected areas - Siyu Qin; Rachel E. Golden Kroner; Carly Cook; Anteneh T. Tesfaw; Rowan Braybrook; Carlos Manuel Rodriguez; Claire Poelking; Michael B. Mascia (Conservation Biology, 2019)
Protected areas (PAs) are expected to conserve nature and provide ecosystem services in perpetuity, yet widespread protected area downgrading, downsizing, and degazettement (PADDD) may compromise these objectives. Even iconic protected areas are vulnerable to PADDD, although these PADDD events are often unrecognized. We identified 23 enacted and proposed PADDD events within World Natural Heritage Sites and examined the history, context, and consequences of PADDD events in 4 iconic PAs (Yosemite National Park, Arabian Oryx Sanctuary, Yasuní National Park, and Virunga National Park). Based on insights from published research and international workshops, these 4 cases revealed the diverse pressures brought on by competing interests to develop or exploit natural landscapes and the variety of mechanisms that enables PADDD. Knowledge gaps exist in understanding of the conditions through which development pressures translate to PADDD events and their impacts, partially due to a lack of comprehensive PADDD records. Future research priorities should include comprehensive regional and country‐level profiles and analysis of risks, impacts, and contextual factors related to PADDD. Policy options to better govern PADDD include improving tracking and reporting of PADDD events, establishing transparent PADDD policy processes, coordinating among legal frameworks, and mitigating negative impacts of PADDD. To support PADDD research and policy reforms, enhanced human and financial capacities are needed to train local researchers and to host publicly accessible data. As the conservation community considers the achievements of Aichi Target 11 and moves toward new biodiversity targets beyond 2020, researchers, practitioners, and policy makers need to work together to better track, assess, and govern PADDD globally.